Threat of bankruptcy and the integrity of financial statement - Omar, Normah; Johar, Zulaikha Amirah; Hasnan, Suhaily (2016)
Financial statement fraud involves the manipulation of financial accounts by overstating assets, sales and profit, understating liabilities and expenses.One of the causes of financial statement fraud is due to threat of bankruptcy. This study explores the effectiveness of Altman Z-Score in predicting the occurrence of financial statement fraud.This study makes a comparison between non-fraudulent companies and fraudulent companies.The sample of non-fraudulent companies is selected from small market capitalization companies in Malaysia.Meanwhile, the sample for fraudulent companies is selected from companies which were charged by the Securities Commission for falsifying financial statements.The result shows that fraudulent companies display sign of bankruptcy before it is charged with falsification of financial statement fraud.